(3NdGUI GdCKQ aj SjQI SjO GdHTQs - (3CMeO Hf CHi HcQ Hf CMeO GdMfaj GdYci GdYQjVis; (3fhQ GdOjf Ydj Hf EHQGgje Hf CMeO GdMdHj GdbGgQj GdTGaYj,J (B1044 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HChUGa GdceGd CeG HYO deG QCjJ GdSjQI GdeSeGI HEfSGf GdYjhf QCjJgG OQQkG fajSI aCMHHJ Cf CMPa ecQQIG hCbOe eDNQgG hSejJ GdeLehY GdeNJUQ , NdGUI GdCKQ s
(3BNQgG (B:s
(3hai gPG GdbOQ caGjI , hcGf JeGe gPg GdNdGUI SfI JSY hYTQjf heGFI hCda s
(3HBNQgG bQGAGJ hJedjcGJ hJbjjOGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdCMbGa ecJHI eMSf Hf LYaQ Hhfei GdNGUI (B((3SjQI (B153(3, (B154) s
Keywords: (3GdJGQjNs